Metal-ligand interactions in a redox active ligand system. Electrochemistry and spectroscopy of [M(dipyvd)2]n+ (M=Zn, Ni, n=0, 1, 2) - Fleming, Connor; Vu, Son; Brook, David J. R.; Agrestini, Stefano; Pellegrin, Eric; DaRos, Jeffrey (Frontiers in Chemistry, 2023)
Reaction of nickel and zinc triflates with the tridentate leucoverdazyl 1-isopropyl-3,5-di (2′-pyridyl)-6-oxo-2H-tetrazine (dipyvdH) and triethylamine resulted in the neutral coordination compounds M(dipyvd)2 (M = Ni,Zn). In acetonitrile, both compounds undergo two one electron oxidation processes, Zn (dipyvd)2 at −0.28 V and −0.12 V and Ni(dipyvd)2 at −0.32 V and −0.15 V vs ferrocene/ferricenium. Oxidations are ligand based resulting in an intermediate mixed valence species and a cationic bis(verdazyl) compound respectively. Oxidation of the ligand changes a localized, antiaromatic, non-planar 8π electron anion to a planar, delocalized 7π electron radical. The change in ligand structure results in an increase in the octahedral ligand field splitting from 10,500 cm–1 to ∼13,000 cm–1, suggesting an increase in the pi acceptor character of the ligand. In the mixed valence species, spectroscopic data suggests minimal interaction between ligands mediated by the metal center; i.e., these are class I-II systems in the Robin-Day classification.